Enhancing the Antibiotic Antibacterial Effect by Sub Lethal Tellurite Concentrations: Tellurite and Cefotaxime Act Synergistically in Escherichia Coli - Vasquez-Guzman, C; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Muñoz-Villagran, C; Molina-Quiroz, R (2012)
Sin Editorial Disponible